2007
DOI: 10.1093/toxsci/kfm256
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondrial and Oxidative Injury in BDE 47 Toxicity to Human Fetal Liver Hematopoietic Stem Cells

Abstract: The polybrominated diphenyl ethers (PBDEs) are a group of flame retardants whose residues have markedly increased in the environment and in human tissues during the last decade. Of the various congeners, BDE 47 (2,2',4,4'-tetrabromodiphenyl ether) is typically the predominant congener observed in fish and wildlife samples, as well as in human tissues. Several studies indicate in utero transfer of PBDEs during pregnancy with residues accumulating in fetal tissues, and thus the potential for BDE 47-mediated inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 56 publications
4
62
1
2
Order By: Relevance
“…In terms of PBDE toxicity, it has also been proposed that one of mechanisms is an increased formation of reactive oxygen species (ROS). Studies have demonstrated that PBDEs can induce oxidative stress in neuronal cells (Costa and Giordano, 2007), in addition to mammals, bird and fish hepatocytes (Fernie et al, 2005;Raldúa et al, 2008;Shao et al, 2008;Albina et al, 2010;Zhao et al, 2011). Consequently, oxidative stress could contribute to the alternation of retinoids and increase the utilization of retinol as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of PBDE toxicity, it has also been proposed that one of mechanisms is an increased formation of reactive oxygen species (ROS). Studies have demonstrated that PBDEs can induce oxidative stress in neuronal cells (Costa and Giordano, 2007), in addition to mammals, bird and fish hepatocytes (Fernie et al, 2005;Raldúa et al, 2008;Shao et al, 2008;Albina et al, 2010;Zhao et al, 2011). Consequently, oxidative stress could contribute to the alternation of retinoids and increase the utilization of retinol as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…cells (He et al, 2008a,b;Shao et al, 2008). However, little information exists about the possible toxic mechanisms induced by of PBDEs.…”
Section: Discussionmentioning
confidence: 99%
“…There is supporting evidence for the ability of PBDEs to induce oxidative stress. BDE-47 was reported to cause oxidative stress in different cells, such as human neutrophil granulocytes (Reistad and Mariussen, 2005), human neuroblastoma cells (He et al, 2008b), hippocampal neurons (He et al, 2008a), and human fetal hematopoietic cells (Shao et al, 2008). While BDE-209 was shown to increase oxidative stress in human hepatoma cells Hep G2 (Hu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress was determined fluorometrically using diclorofluorescein (DCF) (Said et al 2007); (Shao et al 2008 nm and emission at 520 nm) were taken from 0.5 h -24 h using a BMG Polarstar fluorimetric plate reader. Measurements were recorded for 4 independent cultures.…”
Section: Oxidative Stress Measurement Using a Diclorofluorescein (Dcfmentioning
confidence: 99%